اعداد القوائم الاستنادیة "مشروع اعداد قائمة استنادیة للأسماء بادارة المخطوطات والمکتبات الاسلامیة - د. أحمد أحمد محمد المزین (المجلة الدولية لعلوم المكتبات والمعلومات)
This paper deals with the subject of authority control, especially thecontrol of Arabic names and the preparation of authority lists for the names ofpeople, This is because it is of great importance to the staff in the field of librariesand information, and also to use it to retrieve information sources, And for thatpurpose a definition of authority control has been introduced, Highlighting itsimportance, objectives, functions, tools, outputs and types of authority files andtheir forms, With reference to the experiences of some Arab and foreign librariesin the authority control projects, The researcher adopted a case studymethodology to identify the features of the project of preparing a list authority ofArabic names for the Department of manuscripts and Islamic libraries in the Stateof Kuwait, The most important findings of the study are the results of theimportance of authority control in the process of retrieving sources of informationand the shortage of specialized persons in the field of authority control, andnecessity Develop a strategy for inter-library cooperation to create a unifiedArabic authority file for both ancient and modern Arabic names It is co-foundedby members from all Arab countries.